The comparison of some depigmentation techniques towards reccurence of gingival hyperpigmentation: a systematic review - Hardianti Maulidita Haryo; Arni Irawaty Djais; Andi Mardiana Adam (Makassar Dental Journal PDGI Makassar, 2020)
Objective: To compare the best gingival depigmentation technique toward the recurrence of gingival hyperpigmentation. Methods: PubMed and Wiley Online Library were conducted to identify articles from January 2013 to November 2018 about the techniques of depigmentation gingiva in patient with gingiva hyperpigmentation. After the selection of articles, 121 articles were obtained but only 3 articles meet the requirements. Dummett oral pigmentation index (DOPI) and Hedin melanin index (HMI) were used to compare the techniques of gingival depigmentation. Results: The clinical parameters have shown reduction of the pigmentation from a patient, in 1, 3 and 6 months. In the second article showed the DOPI only in baseline and 6 months. In third article showedthe DOPI only in baseline and 1 month. Conclusion: The conventional surgical technique eliminates all the hyperpigmentation and showed the less recurrence.